Стан вивчення умов праці провідників - Цуркан, В.Г. (Актуальні проблеми транспортної медицини, 2009)
На основании собственных и литературных данных предложена и обсуждена схема основных задач по исследованию проблемы гигиены труда и профессиональной патологии проводников пассажирских вагонов. The author’s own and literature data form a background for setting forth and discussing a schematic list of basic problem in the domain of investigations concerned with the issues pathology of guard of passenger long – distance trains.